Impact of PD-L1 expression and human papillomavirus status in anti-PD1/PDL1 immunotherapy for head and neck squamous cell carcinoma—Systematic review and meta-analysis - Patel, Jaimin J. (Head Neck, 2019)
Programmed cell death-1 (PD-1) pathway inhibition in head and neck squamous cell carcinoma (HNSCC) has demonstrated inconsistent efficacy regarding human papillomavirus (HPV) status and PD-L1 expression. This study compared outcomes in HNSCC in the context of PD-L1 and HPV expression. Outcomes: PD-L1 and HPV expression; overall survival (OS), and tumor response (ORR). 1088 patients received PD-1/L1 inhibitors. Four methodologies were identified in determining PD-L1 expression, most commonly using the Dako PD-L1 IHC 22C3 pharmaDx assay. Using a 1% threshold, ORR was greater for PD-L1 expressers vs non-expressers (18.9%, CI 16.1–21.8 v 8.8% CI 5.3–13.7, P = 0.009), as was OS at 6 months (60.6%, CI 49.2–71.4 v 49.0%, CI 39.1–59.0, P = 0.04) but not at 12 or 18 months. No advantages were identified for HPV expressers. Patients expressing PD-L1 may have a better tumor response and OS. No impact on survival or response was observed based on HPV status.